Dois paradigmas para o enfrentamento da crise ética do século XX: a alteridade em Emmanuel Levinas e a revolta em Albert Camus. - Oliveira, Alberto Luiz Silva de (2022)
The present research presented here has as its main reflective element the crisis of ethical and moral values that have taken the center of ethical reflection in recent centuries. The ethical crisis as mentioned above refers to the fraying of the moral values that for many centuries guided Western culture, its politics and its spirituality. The 20th century was taken as a starting point and historical cut because it is precisely a period where the crisis proves to be extremely virulent for the maintenance of human life and civilization. The period of the two great wars, followed by the tensions of the cold war are the scenario where nihilism, murder and ideological terror dictate ethical concerns that extend to the present day. The reader will find in the first chapter of this dissertation some theoretical elements that illuminate the severity of the crisis and from these clippings the objective is to demonstrate the ethical crisis as well as from the reflections of Emmanuel Levinas and Albert Camus to illuminate possible paths for a reconciliation between the human beings divided by violence and terror. In order to fulfill these demands, we analyzed the biography of these two authors who lived through this period and based on the concept of Alterity in Levinas and Revolt in Camus, we highlight the ethical pretensions made by each author in coping with the symptoms of the crisis in the following two chapters of the dissertation. This allowed us to reach some answers and support other questions that were not exhausted in this research work.